2018
DOI: 10.14202/vetworld.2018.1404-1408
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between bacterial sources and genotype to the antimicrobial resistance pattern of Burkholderia pseudomallei

Abstract: Background:Melioidosis is a fatal emerging infectious disease of both man and animal caused by bacteria Burkholderia pseudomallei. Variations were suggested to have existed among the different B. pseudomallei clinical strains/genotypes which may implicate bacterial susceptibility and resistance toward antibiotics.Aim:This study was designed to determine whether the phenotypic antibiotic resistance pattern of B. pseudomallei is associated with the source of isolates and the genotype.Materials and Methods:A coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…Although, meropenem and imipenem are used as an alternative to ceftazidime [26], meropenem and imipenem showed 100 % susceptibility, except for meropenem for human isolates (98.9 %) and imipenem for soil sources (90.9 %). The susceptibility rate for meropenem and imipenem in our study was higher than previous studies, which reported 100% susceptibility for imipenem [25]. Ciprofloxacin, a member of fluoroquinolones, was used individually or combined with doxycycline to treat acute melioidosis [27].…”
Section: Humancontrasting
confidence: 52%
See 2 more Smart Citations
“…Although, meropenem and imipenem are used as an alternative to ceftazidime [26], meropenem and imipenem showed 100 % susceptibility, except for meropenem for human isolates (98.9 %) and imipenem for soil sources (90.9 %). The susceptibility rate for meropenem and imipenem in our study was higher than previous studies, which reported 100% susceptibility for imipenem [25]. Ciprofloxacin, a member of fluoroquinolones, was used individually or combined with doxycycline to treat acute melioidosis [27].…”
Section: Humancontrasting
confidence: 52%
“…There were many patterns of antimicrobial drug resistance of B. pseudomallei in our study as shown in Table 4. Monitoring of antimicrobial resistance of B. pseudomallei isolates, not only in clinical specimens but also in animal and environmental isolates, needs to be conducted regularly to guide empiric therapy for human melioidosis, as it causes high mortality [25]. We found that mono-resistance to ceftazidime, the first drug of choice in the acute phase for melioidosis treatment, was 3.0 % of B. pseudomallei from soil sources.…”
Section: Humanmentioning
confidence: 94%
See 1 more Smart Citation